Biblioteca escolar : análise qualitativa na BDTD de uma década de produção de conhecimento nas áreas de Ciência da Informação, Educação e Letras (2010-2020) - Correia, Érica Mariza (2021)
This dissertation highlights the library as an essential space to construct knowledge, to access information, and to improve the quality of teaching, by encouraging reading, research, literacy and the critical and interpretative development of each student, which already possesses intrinsic knowledge and experiences. As its research problem, it poses the question: How do the dissertations and theses of the areas of Information Science, Education and Modern Languages present the theme of the school library?. For that, the general objective is to present the state of the art of the school library theme in these areas of knowledge, having as a guideline the Law nº 12.244/2010. As specific objectives are: to demonstrate the benefits of the school library in the context of learning in the areas of Information Science, Education and Modern Languages; to develop an orientation booklet for the faculty of the Education and Letters courses at Federal University of Sergipe; and to promote the booklet dissemination, with the aim of expanding teachers' knowledge about the school library potential into learning. This promotion thus diffuses the school library's beneficial role in the process of information literacy, besides highlighting it as an enriching and welcoming space that makes learning increasingly significant and makes education a more egalitarian process. The research takes on a qualitative approach, besides being bibliographic and descriptive, presenting the state of the art in the subject of the school library available on the Brazilian Digital Library of Theses and Dissertations from 2010 to 2020. The booklet production is the final product of this professional master’s degree, which will be made available to the Education and Human Sciences Center´s departments in the Federal University of Sergipe, as well as to the Application School teachers, which is linked to the same university. Access to libraries, from an early age, makes individuals more autonomous and protagonists of their own learning. In this way, it expands the cultural, social and human aspect inherent to every human being, who needs to know how to deal with the complexity of life. Then, further studies on the subject are necessary, since this research shows that the school library is indeed significant and requires bigger visibility in the different areas of knowledge.